Brand personality and revisit intention: The mediating role of tourists’ self-image congruity - Duc Thang Nguyen; Thi Thu Huong Nguyen; Kieu Oanh Nguyen; Thi Thanh Hang Pham; Thu Huong Nguyen (Tourism and Hospitality Management, 2023)
Purpose – Brand personality plays an important role in the development of tourists’ self-image congruence and revisit intention. This paper attempts to shed light on the relationship between brand personality and self-image congruence and revisit intention through a quantitative analysis. Design – Data were collected from 496 Vietnamese tourists who visited the top five tourist sites in Vietnam, including Ha Long, Phu Quoc, Sapa, Nha Trang, and Hoi An. Methodology – By using SEM in AMOS version 24 CFA was performed to test the the overall measurement model. Findings – Multivariate data analysis demonstrated that five dimensions of brand personalitỵ (Excitement, Sincerity, Sophistication, Competence, and Ruggedness) have a positive effect on self-image congruence and revisit intention. While excitement appears to be most helpful for developing self-image congruence, sincerity has the highest benefit for increasing revisit intention, sincerity has the highest utility for increasing revisit intention. In addition, revisit intention is most influenced by excitement and least influenced by sophistication through selfimage congruence. Originality of the research – The findings highlight the important role of attributes associated with tourist destinations. Managers in the tourism sector should be familiar with these characteristics in order to position or strengthen their destination’s brand with the aim of delivering to each tourist group a customized experience that resonate with their shared values. The insights provided by this paper also have important implications for travel companies in the gradual recovery of the country’s smoke-free industry under the conditions of the COVID -19 pandemic.